Coxiella burnetii-containing vacuoles interact with host recycling endosomal proteins Rab11a and Rab35 for vacuolar expansion and bacterial growth - Hall, Brooke A.; Senior, Kristen E.; Ocampo, Nicolle T.; Samanta, Dhritiman (Frontiers in Cellular and Infection Microbiology, 2024)
Coxiella burnetii is a gram-negative obligate intracellular bacterium and a zoonotic pathogen that causes human Q fever. Although acute Q fever manifests as atypical pneumonia, chronic infection may lead to life-threatening endocarditis. The lack of effective antibiotics and a licensed vaccine for Coxiella in the U.S. warrants further research into Coxiella pathogenesis. Within the host cells, Coxiella replicates in an acidic phagolysosome-like vacuole termed Coxiella-containing vacuole (CCV). Previously, we have shown that the CCV pH is critical for Coxiella survival and that the Coxiella Type 4B secretion system regulates CCV pH by inhibiting the host endosomal maturation pathway. However, the trafficking pattern of the ‘immature’ endosomes in Coxiella-infected cells remained unclear. Our recent CCV localization screen with host Rab proteins revealed that recycling endosome-associated proteins Rab11a and Rab35 localize to the CCV during infection, suggesting that CCV interacts with host recycling endosomes during maturation. Interestingly, only a subset of CCVs were Rab11a or Rab35-positive at any given time point. A quantitation of Rab11a/Rab35-positive CCVs revealed that at 3 dpi, 52% of CCVs were positive for Rab11a, and 39% CCVs were positive for Rab35 whereas, at 6-dpi, only 22% of CCVs were positive for Rab11a and 64% of CCVs were positive for Rab35. These data suggest that the CCV preferentially interacts with Rab11a and Rab35 depending on the stage of infection. We also observed a significant increase in Rab11a and Rab35 fluorescent intensity in Coxiella-infected cells compared to mock cells suggesting that Coxiella increases the recycling endosome content in infected cells. Finally, siRNA-mediated knockdown of Rab11a and Rab35 resulted in significantly smaller CCVs and reduced Coxiella intracellular growth, suggesting that recycling endosomal Rab proteins are essential for CCV expansion and bacterial multiplication. Overall, our data, for the first time, show that the CCV dynamically interacts with host recycling endosomes for Coxiella intracellular survival and potentially uncovers novel host cell factors essential for Coxiella pathogenesis.